2019
DOI: 10.1128/aem.02534-18
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and Functional Compositions of the Small Intestinal Microbiome in Neonatal Calves Provide a Framework for Understanding Early Life Gut Health

Abstract: A lack of information on the intestinal microbiome of neonatal calves prevents the use of microbial intervention strategies to improve calf gut health. This study profiled the taxonomic and functional composition of the small intestinal luminal microbiome of neonatal calves using whole-genome sequencing of the metagenome, aiming to understand the dynamics of microbial establishment during early life. Despite highly individualized microbial communities, we identified two distinct taxonomy-based clusters from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 53 publications
9
47
0
1
Order By: Relevance
“…Like Lactobacillus, Akkermansia is currently considered to be a beneficial microbe [42]. Our previous study reported that probiotic or prebiotic therapy that protected adult offspring against hypertension programmed by maternal high-fructose diet was related to increases of the abundance of Akkermansia [46]. Given that NAC increased fecal H 2 S levels, additional studies are required to clarify whether this discrepancy is a compensatory reduction of sulfur-metabolizing Akkermansia abundance in response to excessive colonic H 2 S. Although gut-derived H 2 S has been proposed for producing a systemic effect on BP [13], according to our data the protective effect of NAC on hypertension is mainly attributed to SOB and thiosulfate.…”
Section: Discussionmentioning
confidence: 99%
“…Like Lactobacillus, Akkermansia is currently considered to be a beneficial microbe [42]. Our previous study reported that probiotic or prebiotic therapy that protected adult offspring against hypertension programmed by maternal high-fructose diet was related to increases of the abundance of Akkermansia [46]. Given that NAC increased fecal H 2 S levels, additional studies are required to clarify whether this discrepancy is a compensatory reduction of sulfur-metabolizing Akkermansia abundance in response to excessive colonic H 2 S. Although gut-derived H 2 S has been proposed for producing a systemic effect on BP [13], according to our data the protective effect of NAC on hypertension is mainly attributed to SOB and thiosulfate.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested colonization of the mammalian GIT begins during the birthing process, with the fetus exposed in utero to maternal and environmental microbiota following cervical dilation and rupture of amniotic membranes. Similar to neonatal calves (Malmuthuge, 2016; Malmuthuge et al, 2019), the microbiome in the small intestine of newborn lambs was dominated by Proteobacteria with a transition to Firmicutes with increasing age and exposure to ingesta. Massilia (phylum Proteobacteria ) was one of the abundant bacterial genera observed in the small intestine of newborn lambs, including both the adjacent intact small intestine and the surgically isolated intestinal segments (Supplementary Figure 1A).…”
Section: Discussionmentioning
confidence: 95%
“…A correlation-based hierarchical clustering approach (Malmuthuge et al, 2019) was used to explore similarities or dissimilarities of the total bacterial communities profiled from three intestinal segments. First, a Spearman rank correlation analysis was performed using the cor() function in R to obtain correlation (ρ) between each pair of small intestinal microbial profiles based on the relative abundance of OTUs clustered at 97% similarity.…”
Section: Methodsmentioning
confidence: 99%
“…The seasonal variations in microbiome composition in our study are likely due to seasonal changes in diets. Diet is an important factor that shapes gut microbial communities [36][37][38]. Speci cally, the ratio of ber to carbohydrates in diets can impact microbiome composition in ruminants [39].…”
Section: Discussionmentioning
confidence: 99%